Acquisition of value-based competencies for effective management of training of specialists - Ivanova, Maryna; Shvets, Vasyl; Varianychenko, Olena; Sannikova, Svitlana (Management and Entrepreneurship: Trends of Development, 2022)
The purpose of this study is to examine the features of the acquisition of value-based competencies for effective management of training of specialists. Higher education institutions are tasked with implementing educational programs that allow to achieve the set goals and form the necessary competencies to provide quality training of specialists. An analysis of recent research and publications has shown that the use of the competency approach in higher education institutions has become possible owing to the new standards approved by the Ministry of Education and Science. Methodology: General scientific and special methods of system-structural analysis and synthesis, frequency analysis, quantitative distribution, grouping were used in the research process. Competencies which the applicants for higher education are supposed to acquire after mastering the educational and professional programs were analyzed in each specialty. The research findings show that the main components of professional education are 11 core competencies, which account for 35% of all competencies studied and form 68% of universal skills in all specialties, while 22 competencies are unique to educational and professional programs and provide performing professional functions by type of activity. It has been found that in the specialties of natural sciences, engineering and information technologies, the main emphasis is placed on the acquisition of purely professional competencies, while in humanities, economic, managerial and law specialties, professional competencies are supplemented with intercultural and social competencies. The grouping of competencies according to the opportunity to obtain learning outcomes has been given, the understanding of the grouping allows to provide effective management of quality training of specialists. JEL Classification: A22, I20.